Permissive versus restrictive temperature thresholds in critically ill children with fever and infection: a multicentre randomized clinical pilot trial - Peters, Mark J.; Woolfall, Kerry; Khan, Imran; Deja, Elisabeth; Mouncey, Paul R.; Wulff, Jerome; Mason, Alexina; Agbeko, Rachel S.; Draper, Elizabeth S.; Fenn, Blaise; Gould, Doug W.; Koelewyn, Abby; et al. (Critical care (London, England), 2019)
Fever improves pathogen control at a significant metabolic cost. No randomized clinical trials (RCT) have compared fever treatment thresholds in critically ill children. We performed a pilot RCT to determine whether a definitive trial of a permissive approach to fever in comparison to current restrictive practice is feasible in critically ill children with suspected infection. An open, parallel-group pilot RCT with embedded mixed methods perspectives study in four UK paediatric intensive care units (PICUs) and associated retrieval services. Participants were emergency PICU admissions aged > 28 days to < 16 years receiving respiratory support and supplemental oxygen. Subjects were randomly assigned to permissive (antipyretic interventions only at ≥ 39.5 °C) or restrictive groups (antipyretic interventions at ≥ 37.5 °C) whilst on respiratory support. Parents were invited to complete a questionnaire or take part in an interview. Focus groups were conducted with staff at each unit. Outcomes were measures of feasibility: recruitment rate, protocol adherence and acceptability, between group separation of temperature and safety. One hundred thirty-eight children met eligibility criteria of whom 100 (72%) were randomized (11.1 patients per month per site) without prior consent (RWPC). Consent to continue in the trial was obtained in 87 cases (87%). The mean maximum temperature (95% confidence interval) over the first 48 h was 38.4 °C (38.2-38.6) in the restrictive group and 38.8 °C (38.6-39.1) in the permissive group, a mean difference of 0.5 °C (0.2-0.8). Protocol deviations were observed in 6.8% (99/1438) of 6-h time periods and largely related to patient comfort in the recovery phase. Length of stay, duration of organ support and mortality were similar between groups. No pre-specified serious adverse events occurred. Staff (n = 48) and parents (n = 60) were supportive of the trial, including RWPC. Suggestions were made to only include invasively ventilated children for the duration of intubation. Uncertainty around the optimal fever threshold for antipyretic intervention is relevant to many emergency PICU admissions. A more permissive approach was associated with a modest increase in mean maximum temperature. A definitive trial should focus on the most seriously ill cases in whom antipyretics are rarely used for their analgesic effects alone. ISRCTN16022198 . Registered on 14 August 2017.